2015
DOI: 10.1002/nau.22784
|View full text |Cite
|
Sign up to set email alerts
|

Does pelvic floor muscle training augment the effect of surgery in women with pelvic organ prolapse? A systematic review of randomized controlled trials

Abstract: Insufficient evidence was found to support adding perioperative PFMT to surgery over the use of surgery alone in women undergoing surgery for POP. Adequately, powered RCTs with longer follow-up periods are required to evaluate the long-term effect of perioperative PFMT. Neurourol. Urodynam. 35:666-674, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
14
0
3
Order By: Relevance
“…Considering the results of the control groups without PFMT of the RCTs included in the systematic review of Zhang et al it is not possible to conclude if PFM strength changes postsurgery. Only two studies verified a small decrease in manometry values 3 months post POP surgery with no statistical analysis available.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the results of the control groups without PFMT of the RCTs included in the systematic review of Zhang et al it is not possible to conclude if PFM strength changes postsurgery. Only two studies verified a small decrease in manometry values 3 months post POP surgery with no statistical analysis available.…”
Section: Discussionmentioning
confidence: 99%
“…40 Without confidently knowing the effect of surgery on PFM morphometry and function, it is difficult to conclude that perioperative PFM training is required, and if so, when it would be most beneficial. The most recent reviews of perioperative PFM training for women undergoing prolapse surgery 22,50 found no significant improvement in prolapse symptoms, degree of prolapse or quality of life with the addition of PFM training. A possible reason for the lack of clear effect in both of these reviews and this one could be that women with poorer preoperative PFM function 18,19,[51][52][53] (at risk group), were not specifically targeted.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this body of research, PFPT is recommended as the first‐line treatment for women with pelvic organ prolapse (Grade A Recommendation); however, more research is needed to understand what PFPT regimens are most effective in managing pelvic organ prolapse, the cost‐effectiveness of PFPT in the treatment of pelvic organ prolapse, and how long benefits persist after treatment . For women undergoing surgery for the treatment of prolapse, it is unclear whether adding perioperative PFPT to surgery is superior to surgery alone …”
Section: Pelvic Organ Prolapsementioning
confidence: 99%
“…39 For women undergoing surgery for the treatment of prolapse, it is unclear whether adding perioperative PFPT to surgery is superior to surgery alone. 40 Health care providers may inform women that it is difficult to predict how well they may respond to PFPT. This therapy increases muscle strength and endurance and results in objective and subjective improvements in prolapse symptoms, but it does not predict or always prevent the need for further treatment.…”
Section: Pfpt Management Of Pelvic Floor Prolapsementioning
confidence: 99%